Sports instructors, job satisfaction - Bastidas Alcívar, RJ.; Angosto Sánchez, S.; Martínez Moreno, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
The objective of the study is to determine the level of job satisfaction in sports monitors, through quantitative, descriptive and transversal research. Descriptive analyses, mean, percentages and standard deviation were carried out. The sample consisted of 26 monitors, 18 men and 8 women, with an average age of 27.5 (±5.4). The Font Roja job satisfaction questionnaire was used as an instrument, made up of 23 items, grouped into 7 factors, with a Likert scale of 5 anchors, from 1 (totally disagree) to 5 (totally agree). Men are more satisfied 53.7% (±10.5) than women and workers in private companies 60.9% more than those in public companies. As a conclusion to determine that the monitors are moderately satisfied, 50.8% (±10.2) with their work, a fact that may have an impact on the company’s results